TAXONOMIC NOTES ON THE HOVER WASP GENUS EUSTENOGASTER (VESPIDAE, STENOGASTRINAE), WITH DESCRIPTION OF TWO NEW SPECIES FROM SUMATRA ISLAND, INDONESIA - Fuki Saito-Morooka; Hari Nugroho; Alan Handru; Jun-ichi Kojima (Treubia, 2020)
Wasps of the genus Eustenogaster van der Vecht, 1969, with 17 species currently recognized, are distributed from the Indian subcontinent in the west to the Philippines, Sulawesi Island and Java Island in the east. Two new species of hover wasp genus Eustenogaster (E. multifolia sp. nov., E. sumatraensis sp. nov.) are described from specimens collected in Sumatra Island. The female of E. vietnamensis occurring in Vietnam are described for the first time. The lectotypes of Paravespa eva Bell, 1936 and Ischnogaster ornatifrons Cameron, 1902 are designated. The new taxonomic status is proposed for Stenogaster eximioides Dover and Rao, 1922 as a good (=valid) species of Eustenogaster. The synonymy of Ischnogaster ornatifrons Cameron, 1902 with Eustenogaster micans (de Saussure, 1852) has been confirmed. A revised key to species and a taxonomic and distributional checklist of all the species of Eustenogaster are provided.